2019
DOI: 10.1097/qai.0000000000002157
|View full text |Cite|
|
Sign up to set email alerts
|

Definition of Immunological Nonresponse to Antiretroviral Therapy: A Systematic Review

Abstract: Background: Terms and criteria to classify people living with HIV on antiretroviral therapy who fail to achieve satisfactory CD4+ T-cell counts are heterogeneous, and need revision and summarization. Methods: We performed a systematic review of PubMed original research articles containing a set of predefined terms, published in English between January 2009 and September 2018. The search retrieved initially 1360 studies, of which 103 were eligible. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 124 publications
0
35
0
4
Order By: Relevance
“…Immunological nonresponse denotes a CD4 + cell count <350 cells/μl despite ART and viral suppression [32]. In our virally suppressed cohort, we found that a CD4 + cell count <350 cells/μl at study entry was associated with de novo PAD, suggesting that immunological nonresponders may potentially be at higher risk.…”
Section: Discussionmentioning
confidence: 66%
“…Immunological nonresponse denotes a CD4 + cell count <350 cells/μl despite ART and viral suppression [32]. In our virally suppressed cohort, we found that a CD4 + cell count <350 cells/μl at study entry was associated with de novo PAD, suggesting that immunological nonresponders may potentially be at higher risk.…”
Section: Discussionmentioning
confidence: 66%
“…Although plasma viral load declines to undetectable levels after initiation of antiretroviral therapy (ART), immune reconstitution may not occur; about 10–40% of HIV-infected individuals fail to normalize CD4 + T cell counts. These patients, known as immunological non-responders (INRs), have severe immune dysfunction with CD4 + T cell counts < 500 or < 350 cells/μL, or in extreme cases, < 200 cells/μL [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the selected subjects, 120 were considered controls (baseline CD4 + T-cell counts >200 cells/µL), and 101 were cases (baseline CD4 + T-cell counts ≤ 200 cells/µL). At 144 weeks, cases were classified according to the cut-off of 250 CD4 + T cells [2,57]. Among the cases, 77 subjects (76.2%) achieved a value of more than 250 CD4 + T cells/µL after 144 weeks of ART ("immunological recoverers", IR), whereas 22 subjects (21.8%) did not reach the 250 CD4 + T cells/µL threshold ("immunological nonrecoverers", INRs).…”
Section: Study Design and Participantsmentioning
confidence: 99%